Initial Report of Second‐Line FOLFIRI in Combination with Ramucirumab in Advanced Gastroesophageal Adenocarcinomas: A Multi‐Institutional Retrospective Analysis - Klempner, Samuel J.; Maron, Steven B.; Chase, Leah; Lomnicki, Samantha; Wainberg, Zev A.; Catenacci, Daniel V.T. (The oncologist (Dayton, Ohio), 2019)
Background The randomized phase III RAINBOW trial established paclitaxel (pac) plus ramucirumab (ram) as a global standard for second‐line (2L) therapy in advanced gastric and gastroesophageal junction adenocarcinoma, together gastroesophageal adenocarcinoma (GEA). Patients (pts) receiving first‐line (1L) FOLFOX often develop neuropathy that renders continued neurotoxic agents in the 2L setting unappealing and other regimens more desirable. As such, FOLFIRI‐ram has become an option for patients with 2L GEA. FOLFIRI‐ramucirumab (ram) has demonstrated safety and activity in 2L colorectal cancer, but efficacy/safety data in GEA are lacking. Subjects, Materials, and Methods Patients with GEA treated with 2L FOLFIRI‐ram between August 2014 and April 2018 were identified. Clinicopathologic data including oxaliplatin neurotoxicity rates/grades (G), 2L treatment response, progression‐free survival (PFS), overall survival (OS), safety, and molecular features were ed from three U.S. academic institutions. Kaplan‐Meier survival analysis was used to generate PFS/OS; the likelihood ratio test was used to determine statistical significance. Results We identified 29 pts who received 2L FOLFIRI‐ram. All pts received 1L platinum + fluoropyrimidine, and 23 of 29 (79%) had post‐1L neuropathy; 12 (41%) had G1, and 11 (38%) had G2. Patients were evenly split between esophagus/gastroesophageal junction (12; 41%) and gastric cancer (17; 59%). Among evaluable pts (26/29), the overall response rate was 23% (all partial response) with a disease control rate of 79%. Median PFS was 6.0 months and median OS was 13.4 months among all evaluable pts. Six‐ and 12‐month OS were 90% (n = 18/20) and 41% (n = 7/17). There were no new safety signals. Conclusion We provide the first data suggesting FOLFIRI‐ram is a safe, non‐neurotoxic regimen comparing favorably with the combination of pac + ram used in the seminal RAINBOW trial. Implications for Practice Results of this study provide initial support for the safety and efficacy of second‐line (2L) FOLFIRI‐ramucirumab (ram) after progression on first‐line platinum/fluoropyrimidine in patients with gastroesophageal adenocarcinoma (GEA). The overall response, progression‐free survival, overall survival, and toxicity profile compare favorably with paclitaxel (pac) + ram and highlight the importance of the ongoing phase II RAMIRIS trial examining FOLFIRI‐ram versus pac + ram in 2L GEA (NCT03081143). FOLFIRI‐ram may warrant consideration for inclusion as an alternate regimen in consensus guidelines for GEA. 摘要 背景。随机 III 期 RAINBOW 试验制定了紫杉醇 (pac) 和雷莫芦单抗 (ram) 作为晚期胃部和胃食管结合部腺癌，统称为胃食管腺癌 (GEA)，二线 (2L) 治疗的全球标准。接受一线 (1L) FOLFOX 治疗的患者 (pt) 通常会出现神经病变，这使得在 2L 环境中持续使用神经毒剂不具吸引力，而其他疗法则更为可取。因此，FOLFIRI‐雷莫芦单抗 (ram) 成为 2L GEA 患者的一种选择。FOLFIRI‐ ram已在 2L 结直肠癌治疗中显示出安全性和活性，但是，在 GEA 治疗中尚缺乏有效性/安全性数据。 受试者、材料和方法。我们找出在 2014 年 8 月至 2018 年 4 月期间接受 2L FOLFIRI‐ram 治疗的 GEA 患者。从三个美国学术机构中提取包括奥沙利铂神经毒性率/等级 (G)、2L 治疗反应、无进展生存期 (PFS)、总生存期 (OS)、安全性以及分子特性在内的临床病理数据。Kaplan‐Meier 生存分析用于生成 PFS/OS；似然比检验用于确定统计显著性。 结果。我们找到 29 名接受 2L FOLFIRI‐ram 治疗的患者。所有患者均接受 1L 铂类 + 氟尿嘧啶类治疗，29 名患者中的 23 名患者 (79%) 出现 1L 后神经病变；12 名患者 (41%) 为 G1，11 名患者 (38%) 为 G2。患者均匀地分布于食道/胃食管结合部癌症(12 名患者；41%)和胃癌(17 名患者；59%)之间。在可评价的患者(29 名患者中的 26 名患者)中，总缓解率为 23%(全部为部分缓解)，疾病控制率为 79%。在所有可评价的患者中，中位 PFS 为 6.0 个月，中位 OS 为 13.4 个月。6 个月 OS 和 12 个月 OS 分别占 90% (n = 18/20) 和 41% (n = 7/17)。没有新的安全信号。 结论。我们提供了首个数据表明 FOLFIRI‐ram 是一种不会毒害神经的安全疗法，可以与创新性 RAINBOW 试验中使用的 pac + ram 联合治疗相媲美。 实践意义:本研究结果对胃食管腺癌 (GEA) 患者在一线铂类/氟尿嘧啶类治疗出现进展后的二线 (2L) FOLFIRI‐雷莫芦单抗(ram) 治疗提供初步支持。总体反应、无进展生存期、总生存期以及毒性特征可以与紫杉醇 (pac) + ram 相媲美，并强调了旨在于 2L GEA (NCT03081143) 中检验 FOLFIRI‐ram 对比 pac + ram 的正在进行的 II 期 RAMIRIS 试验的重要性。可能值得考虑的是，将 FOLFIRI‐ram 作为一种替代疗法列入 GEA 的共识指南。 FOLFIRI‐Ram has emerged as a reasonable second‐line option for patients with advanced gastroesophageal adenocarcinoma. This article examines the safety and efficacy of second‐line FOLFIRI‐ram across a clinically‐annotated and molecularly characterized U.S. cohort.